Quanto custa pagar tributos? - Bertolucci, Aldo V; Nascimento, Diogo Toledo do (Revista Contabilidade & Finanças, 2002)
The cost of taxation does not include only taxes but also all formal and bureaucratic aspects of taxation that taxpayers have to comply according to the tax legislation. This study began recently in the world and only in 2001 there was a survey in Brazil. This work presents a general vision of the studies worldwide and the results of a survey with public companies in Brazil. The survey confirms the international tendencies and estimates that resources spent in 1999 with Compliance Costs of Taxation reached R 7,2 billion. A more rational fiscal legislation could reduce part of these costs, reducing the operational costs of Brazilian companies.